Declining Inconsistent Condom Use but Increasing HIV and Syphilis Prevalence Among Older Male Clients of Female Sex Workers: Analysis From Sentinel Surveillance Sites (2010–2015), Guangxi, China. Issue 22 (May 2016) - Chen, Yi; Abraham Bussell, Scottie; Shen, Zhiyong; Tang, Zhenzhu; Lan, Guanghua; Zhu, Qiuying; Liu, Wei; Tang, Shuai; Li, Rongjian; Huang, Wenbo; Huang, Yuman; Liang, Fuxiong; et al.
Abstract : Abstract: Clients of female sex workers (CFSWs) are a bridge population for the spread of HIV and syphilis to low or average risk heterosexuals. Most studies have examined the point prevalence of these infections in CFSWs. Limited evidence suggests that older age CFSWs are at a higher risk of acquiring sexually transmitted diseases compared with younger clients. Thus, we sought to describe long-term trends in HIV, syphilis, and hepatitis C (HCV) to better understand how these infections differ by sex worker classification and client age. We also examined trends in HIV, syphilis, and HCV among categories of female sex workers (FSWs). We conducted serial cross-sectional studies from 2010 to 2015 in Guangxi autonomous region, China. We collected demographic and behavior variables. FSWs and their clients were tested for HIV, syphilis, and HCV antibodies. Positive HIV and syphilis serologies were confirmed by Western blot and rapid plasma regain, respectively. Clients were categorized as middle age (40–49 years) and older clients (≥50 years). FSWs were categorized as high-tier, middle-tier, or low-tier based on the payment amount charged for sex and their work venue. Chi-square test for trends was used for testing changes in prevalence over time. By 2015, low-tier FSWs (LTFSWs) accounted for almost half of all FSWs; and they had the highest HIV prevalence at 1.4%. HIV prevalence declined significantly for FSWs (high-tier FSW, P = 0.003; middle-tier FSWs; P = 0.021; LTFSWs, P < 0.001). Syphilis infections significantly declined for FSWs ( P < 0.001) but only to 7.3% for LTFSWs. HCV and intravenous drug use were uncommon in FSWs. HIV prevalence increased for older age clients (1.3%–2.0%, P = 0.159) while syphilis prevalence remained stable. HCV infections were halved among older clients in 3 years (1.7%–0.8%, P < 0.001). Condom use during the last sexual encounter increased for FSWs and CFSWs. Few clients reported sex with men or intravenous drug use. Clients preferred LTFSWs, especially older clients (81.9%). Our results suggest that HIV and syphilis infections are increasing in older clients who prefer LTFSWs. HIV and syphilis are likely increasing in Guangxi Province through heterosexual transmission.